Sustainability and Bioclimatic Design Principals in Hot-Dry Area of Iran - Mikaeili, Mahshid; Sarıhan, Faruk (ICONARCH International Congress of Architecture and Planning, 2014)
Today, buildings worldwide account for up to 40% of total end-use energy. Sustainable architecture is a general term that described environmentally conscious design techniques in architecture and landscape design. The aims of sustainable architecture at producing buildings that adapted to climate, local, cultural and environmental contexts. Sustainable architecture also referred as Green Architecture, Energy Conscious, Eco friendly, Energy Efficient is a design that uses natural building materials that are energy efficient and that make little or no impact on the nature of a site and its resources. Climate has a major effect on the energy consumption in building. Bioclimatic design in vernacular architecure aims to lower energy consumption, based on the understanding of the climatic parameters that influence the energy behavior of a building. It requires knowledge of the relation between the building’s envelope and the local environment. Reducing energy consumption, using natural resources and providing comfortable, and sustainable living spaces are the aims of bioclimatic design or climatically responsive sustainable building design (vernacular building) in hot-dry areas of Iran.